Тод үсэг судлалын асуудлууд: On the study of Clear Script - О., Самбуудорж (Mongolian Studies, 2023)
In the first part of the article the author states about written language of Modern Mongolian language community and origin of it. For Mongolian language community, cultural relationship that is not ruled by time is written language relationship. Especially at present time it is important to have written language with common orthography for internet communication. In the second part the author stated his view about the reason of Clear script origin, its cultural significance and orthography. He assumed that when /a, d was written after / i/ vowel trait was not appropriate, so that /-/ symbol of length crossly stands for /a, d. For example: band (bariad), bifild (bided) etc. Formerly symbol of length /-/ had role for marking for long vowels, but today it. marks for long vowel and as well as for /a, d vowels depending on writing and reading demand and economy.